Dinamika Kesultanan Panai Tahun 1862 – 1946 - Zuldi Ansari; Sori Monang An-nadwi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Cultural history in East Sumatra, close relationship with interactions between residents and immigrants. North Sumatra is one of the well-known migration destination areas in Indonesia and even Asia, because it is supported by its rapid economic development. The governments of kingdoms and sultanates in the past were founded on the banks of rivers which were the means and source of social and economic life. The Panai Sultanate was one of the sultanates that built a government center on the river bank. Apart from being a strategic location and a source of livelihood. The main focus of this thesis problem is the history of a sultanate that was once established in the city of Labuhanbilik by analyzing the sultanate. This sultanate is called the Panai Sultanate which is located in Labuhanbilik Village, Central Panai District. Another problem is that the author discusses the dynamics of the Panai Sultanate in 1862-1946 and the factors of the destruction of the Panai Sultanate. The type of method used in this research process is the historical research method. Meanwhile, for the approach, the author uses a qualitative approach. In searching for data, this research uses data collection techniques which consist of three types, namely observation, interviews and documentation. The observation technique was carried out by going directly to research locations such as the Panai Grand Mosque, Tengku Kelana Putra Tomb, Labuhanbatu Regency Regional Library, Tengku Luckman Sinar Reading Park, and the area of ​​the former Panai sultanate located in Labuhanbilik Village, Central Panai District. Meanwhile, the interview technique was carried out using interview sessions with informants, namely community leaders from Labuhanbilik Village, staff from the Panai Tengah sub-district office, and officials from the Mabmi Medan office management. And documentation techniques are carried out by collecting sources, both oral and written sources. The results obtained from this research are that the Panai Sultanate was an ethnic Malay Sultanate that was founded around 1670 with the first capital being Kampung Sipege, then Mabar Negeri Lama and finally Labuhanbilik. The Panai Sultanate has a royal leadership lineage of ten kings. The ten kings are Raja Murai, Raja Umu, Raja Muhammad Soleh, Raja Kaharuddin, Raja Abdullah, Raja Muhammad Tahir, Tengku Sulong Syahnara, Tengku Kelana Putra, Tengku Mahmud Aman, and Tengku Hamlet. The Panai Sultanate was destroyed when the social revolution occurred in 1946 in East Sumatra. The fact that can prove the existence of the Panai Sultanate is the existence of the remains of this Sultanate to this day in the form of mosques and tombs.